Comparison of Nursing Staff Calculation Based on the Time and Motion Study and Douglas Method - Purwaningsih Purwaningsih; Khoridatul Bahiyah; Margaretha Kewa Lamak (Jurnal Ners, 2009)
Introduction: The increase of the quality of service requires human resource with good quality and quantity. In health service, nursing staff need can be calculated by using many methods, such as Gillies method, ratio method, nursing workshop method, Thailand and Philippine method, Nina method, and Douglas method. Besides those six methods, nursing staff need can be calculated by calculating worktime and workload. This method is called Time and Motion Study. Douglas method is used to calculate nursing staff need at IRNA Bedah A Dr. Soetomo Hospital. The objective of this study was to compare the calculation of nursing staff need using Douglas method and Time and Motion Study. Method: This study used  descriptive design with observational approach. Samples, taken by total sampling, were 12 nurses at IRNA Bedah A Dr. Soetomo hospital for Time and Motion Study and all patients at IRNA Bedah A. Data for Douglas method were collected by using classification of  patient’s dependence into 3 categories, i.e; self care, partial care, and total care. Data for Time and Motion Study were collected by using observation of nurse’s activities and calculate nurse’s worktime and nurse’s workload. The results showed that according to Douglas method, IRNA Bedah A needed 16 nurses, and according to Time and Motion Study, IRNA Bedah A needed 14 nurses. The mean of patient’s dependence in one week was 13 patients with self care, 3 patients with partial care, and 4 patients with total care. Result: Total productive time of the nurses at IRNA Bedah A was 3.83 hours in the morning, 2.37 hours in the afternoon, and 5.25 hours at night. Nurse’s workload at IRNA Bedah A was 34.62%. It can be concluded that calculation by using method Douglas shows that IRNA Bedah A needs more nurses compared with calculation by using Time and Motion Study. Discussion: Time and Motion Study is more effective than Douglas method to calculate nursing staff need. Most patients at IRNA Bedah A is self care. Most nurse’s activity at IRNA Bedah A is non-productive activity. Most of the nurse’s activities at IRNA Bedah A have done based on the standard of procedure. Nurse’s workload at IRNA Bedah A is underload.